Wide range modulation of synaptic weight in thin-film transistors with hafnium oxide gate insulator and indium-zinc oxide channel layer for artificial synapse application. Issue 26 (23rd June 2021) - Beom, Keonwon; Han, Jimin; Kim, Hyun-Mi; Yoon, Tae-Sik
Abstract : Synaptic transistor with a hafnium oxide gate insulator and an indium–zinc oxide channel layer exhibited wide range synaptic weight modulation with a tunable drain current as an artificial synapse in neuromorphic systems. Abstract : Wide range synaptic weight modulation with a tunable drain current was demonstrated in thin-film transistors (TFTs) with a hafnium oxide (HfO2− x ) gate insulator and an indium–zinc oxide (IZO) channel layer for application to artificial synapses in neuromorphic systems. The drain current in these TFTs was reduced significantly by four orders of magnitude on application of a negative gate bias, then could be restored to its original value by applying a positive bias. The reduced drain current under negative biasing is interpreted as being caused by voltage-driven oxygen ion migration from the HfO2− x gate insulator to the IZO channel, which reduces the oxygen vacancy concentration in the IZO channel. In addition to emulating the analog-type potentiation and depression motions in artificial synapses, the tunable drain current presents paired-pulse facilitation and short-term and long-term plasticity behaviors. These wide-ranging and nonvolatile synaptic behaviors with tunable drain currents are indicative of the potential of the proposed TFTs for artificial synapse applications.